Preclusion / Res Judicata Variables: Nature of the Controversy - Allan D. Vestal (Washington University Law Quarterly, 1965)
The courts and the authorities have reached something of a consensus on the matter of issue preclusion / collateral estoppel. Usually it is stated that such estoppel or preclusion by judgment exists on those issues which were essential to and actually litigated and determined by a valid and final judgment. This statement is obviously an oversimplification of the law. The matter must be examined in greater detail if any meaningful analysis is to be made. First, it is necessary to consider how the courts should ascertain the issues on which there may be preclusion. Secondly, it is necessary to examine the nature of the specific issue involved, for it is clear that the courts are more ready to re-examine some types of issues than others. Finally, it is appropriate to examine the broad nature of the litigation before the court since courts react differently according to the litigation then pending. When all of these factors are considered, it may be possible to articulate some specific conclusions which will give some guidance to the legal profession.
Keywords: Res judicata